Pro- and Anti-fibrogenic Functions of Gram-Negative Bacterial Lipopolysaccharide in the Liver - Gandhi, Chandrashekhar R. (Frontiers in Medicine, 2020)
Extensive research performed over several decades has identified cells participating in the initiation and progression of fibrosis, and the numerous underlying inter- and intra-cellular signaling pathways. However, liver fibrosis continues to be a major clinical challenge as the precise targets of treatment are still elusive. Activation of physiologically quiescent perisinusoidal hepatic stellate cells (HSCs) to a myofibroblastic proliferating, contractile and fibrogenic phenotype is a critical event in the pathogenesis of chronic liver disease. Thus, elucidation of the mechanisms of the reversal to quiescence or inhibition of activated HSCs, and/or their elimination via apoptosis has been the focus of intense investigation. Lipopolysaccharide (LPS), a gut-resident Gram-negative bacterial endotoxin, is a powerful pro-inflammatory molecule implicated in hepatic injury, inflammation and fibrosis. In both acute and chronic liver injury, portal venous levels of LPS are elevated due to increased intestinal permeability. LPS, via CD14 and Toll-like receptor 4 (TLR4) and its adapter molecules, stimulates macrophages, neutrophils and several other cell types to produce inflammatory mediators as well as factors that can activate HSCs and stimulate their fibrogenic activity. LPS also stimulates synthesis of pro- and anti-inflammatory cytokines/chemokines, growth mediators and molecules of immune regulation by HSCs. However, LPS was found to arrest proliferation of activated HSCs and to convert them into non-fibrogenic phenotype. Interestingly, LPS can elicit responses in HSCs independent of CD14 and TLR4. Identifying and/or developing non-inflammatory but anti-fibrogenic mimetics of LPS could be relevant for treating liver fibrosis.